1991
DOI: 10.1159/000186348
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in Canine Leishmaniasis

Abstract: In a prospective survey in the Isle of Elba, 413 dogs affected by naturally acquired Leishmania infantum infection were identified out of a controlled population of 1,500 resident mongrel dogs. In all the 34 randomly selected dogs of different breed, age, and duration of disease, the presence of glomerular lesions which defined mainly two categories of glomerulonephritis (GN) was observed. The first group was characterized by mesangial-cell proliferation either with focal features (11 dogs), or with a diffuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 15 publications
2
25
0
2
Order By: Relevance
“…Our results are in accordance with Poli et al [21] who, in a study of glomerular lesions in dog with CanL, found no correlation between renal involvement and anti- Leishmania titer and creatinine but found correlation between glomerular lesions and the amount of proteinuria. Glomerulopathy that characterized CanL causes proteinuria due to deposition of circulating antigen/antibody complexes; this fact may explain the correlation between UP/UC and IgG value found in our study [18].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with Poli et al [21] who, in a study of glomerular lesions in dog with CanL, found no correlation between renal involvement and anti- Leishmania titer and creatinine but found correlation between glomerular lesions and the amount of proteinuria. Glomerulopathy that characterized CanL causes proteinuria due to deposition of circulating antigen/antibody complexes; this fact may explain the correlation between UP/UC and IgG value found in our study [18].…”
Section: Discussionsupporting
confidence: 93%
“…Histological findings reported in our series are in line with sporadic cases described in humans and in studies on dogs, where type III MPGN was the most commonpattern [15]-[22],[25],[26]. Interestingly, free Leishmania were observed inside the capillary lumen of two patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is probably the result of parasitic dissemination, as reported by other authors in a human kidney transplant recipient [19] and in dogs [25],[26]. Tubular necrosis could be secondary to ischemia due to small vessel obliteration by Leishmania spp.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies in humans, dogs and experimental models have not reported the parasite in the tissues here studied and have only described the histological changes induced in the kidneys DUARTE et al, 1983;OLIVEIRA et al, 1985;CORBETT, 1987;POLI, 1991;NIETO et al, 1992;SALGADO FILHO et al, 2003;PRIANTI et al, 2007;ALBUQUERQUE et al, 2008). Carvalho et al (2007) reported the absence of parasitic forms of Leishmania sp.…”
Section: Discussionmentioning
confidence: 97%